Potential of X-ray endovascular technologies in the correction of rare vascular complications after kidney transplantation - A. V. Shabunin; V. V. Bedin; A. V. Arablinskii; M. G. Minina; V. A. Tsurkan; P. A. Drozdov; I. V. Nesterenko; A. Kh. Tseloeva; Yu. V. Kolbasova; L. P. Semenova; E. Yu. Vetlugina (Трансплантология (Москва))
Objective. The paper aims at demonstrating the efficacy of endovascular interventional techniques in the treatment of rare vascular complications after kidney transplantation.Material and methods. Recipients of renal grafts obtained from a deceased donor developed the following complications: a false aneurysm of the interlobar renal artery after lymphocele puncture in one case and a subintimal hematoma of the external iliac artery with subocclusion of the latter and impaired perfusion of the renal graft in the other one.Results. These complications were successfully managed using X-ray endovascular technologies, which allowed saving the renal grafts in both cases with satisfactory long-term results.Conclusion. Early diagnosis and endovascular technologies made it possible to cope with complications minimally invasively and prevent the development of adverse events in the long term.